May the force (field) be with you: on the importance of conformational searches in the prediction of NMR chemical shifts - (:unkn) unknown (MDPI, 2022)
NMR data prediction is increasingly important in structure elucidation. The impact of force field selection was assessed, along with geometry and energy cutoffs. Based on the conclusions, we propose a new approach named mix-J-DP4, which provides a remarkable increase in the confidence level of complex stereochemical assignments—100% in our molecular test set—with a very modest increment in computational cost.
Keywords: Structural elucidation; Stereochemistry; Nuclear magnetic resonance; Quantum mechanical calculations; Molecular mechanics force field